Developing Guidelines in Clinical Practice for Health Care Providers to Educate the Family Caregivers about the Home-Based Elderly Care for the Emotional and Mental Aspect atSisunthron Health Promoting Hospital, Thalang, Phuket Province - Luevanich, Chayanit (NU Journal of Nursing and Health Sciences, 2019)
This study aimed 1) to develop the clinical practice guideline for health care providers to educate the family caregivers about the home-based elderly care for the emotional and mental aspect at Sisunthron Health Promoting Hospital in Thalang district, Phuket Provinceand, 2) to study the results of applying the clinical practice guideline by the perspective of health care providers'and family caregivers'. The Center for Advanced Nursing Practice Evidenced-Based Practice Model was employed. The model includes four interactive phases namely evidence-triggered, evidence-supported, evidence-observed, and evidence-based phases. The research database from the years 2007-2017 were explored. 24 articles which met the criteria had been reviewed and was the clinical practice guideline developed.The samples included 4 health care providers, 19 home-based elderly, and 19 family caregivers. Questionnaires were used to collect the data, consisting of the comments and the satisfaction questionnaires for the health care providers in applying the clinical practice guideline. The satisfaction among the family caregivers questionnaires, the Patient Health Questionnaire-9 for depression screening and the elderly emotional score. Frequency, percentage, arithmetic mean, standard deviation, Wilcoxon singed rank test for match paired, and content analysis were applied for the data analysis. The results revealed that all health care providers were satisfied with the clinical practice guideline at a high level. After the 5 th home visit, the depression mean scores among the elderly before and after applying the clinical practice guideline were not different. Family caregivers' satisfaction scores before and after applying the clinical practice guideline were statistically significant different at 0.01. and, the elderly's emotional scores before and after applying the clinical practice guideline were statistically significant, different at 0.05.